Determinants of Household Waste Management Behavior in Margagiri Village Bojonegara District Serang Regency - Yanti, Widia; Dini Daningrum (Poltekkes Kemenkes Palu, 2025)
Background: Household waste management is an important issue in Indonesia, especially in rural areas that still face limited facilities and access to information. Poor waste management can trigger environmental pollution and negatively impact public health. This study aims to analyze the factors associated with household waste management behavior in Margagiri Village. Method: This study used a quantitative method with a cross-sectional design. The research was conducted from January to June 2025 in Margagiri Village, Bojonegara Subdistrict, Serang Regency. The sample consisted of 100 housewives selected using a simple random sampling technique. Data were collected through interviews using a structured questionnaire. Data were analyzed using univariate and bivariate analyses with the Chi-Square test. Result: The univariate analysis showed that 56% of respondents had poor household waste management behavior and 61% had a low level of knowledge. A total of 27% of respondents had never received information related to waste management, 21% did not receive support from health workers, 82% were unemployed, and 86% had an income below the regional minimum wage. The bivariate analysis revealed significant relationships between knowledge (p=0.002), information (p=0.000), health worker support (p=0.000), and income (p=0.052) and household waste management behavior. Meanwhile, the employment variable showed no significant relationship. Conclusion: These findings indicate that household waste management behavior is influenced by the level of knowledge, access to information, support from health workers, and income level.